Colonizing Canis lupus: Wolf Management as a Settler Colonial Project - Beggen, Kristina; York, Richard (Rural sociology, 2025)
ABSTRACT The hostility to wolves by segments of agribusiness and the general public in the United States is a puzzle, given that wolf predation is not responsible for a large number of cattle and sheep losses and has only a very modest economic effect on the livestock industry. Thus, the logic of profit‐seeking in capitalism, although playing a role, is insufficient to explain the outsized and partisan opposition to wolf recovery. We argue that the logics of settler colonialism are a foundational force that shapes the politics and management of wolves in the United States. We explain how settler colonialism seeks to eliminate both Indigenous people and wolves to appropriate and reshape landscapes for settler use. Contemporary wolf policy and management at the state and federal levels continue to reflect settler colonial logics. Our general aim is to show how theories of settler colonialism complement other prominent sociological theories and enhance our understanding of the forces leading to ecological crises. We conclude by highlighting examples of more just approaches to wolf management that include Indigenous kinship and relational values.